Strategies for Increasing Community Participation in Education Implementation in Madrasah Aliyah - Lukman Hakim (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to obtain strategies to increase community participation in the implementation of education in Madrasah Aliyah. This research used a descriptive qualitative research method. The nature of the researcher-respondent relationship was revealed by using this method. The research was conducted at Madrasah Aliyah Negeri 1 Mataram. The participants included school principals (N=1) and teachers (20). Data were collected through observation, documentation, and interviews. The data analysis used was Miles and Huberman model, namely data reduction, data presentation, conclusion drawing, and triangulation. The results of the data analysis concluded that Madrasah Aliyah Negeri 1 Mataram provided five strategies to increase community participation in the education process, namely; counselling clinic, academic and non-academic program, building a national-minded character, new student admission, giving equal responsibility to the community for the development of education process. Each strategy involves the participation of a different community. These strategies were designed to achieve educational goals. The results of this study have implications for an in-depth understanding of the principal as the top leader in the school to enable everyone in the school community to participate actively.